Hypokalemia Promotes Arrhythmia by Distinct Mechanisms in Atrial and Ventricular Myocytes. Issue 7 (27th March 2020) - Tazmini, Kiarash; Frisk, Michael; Lewalle, Alexandre; Laasmaa, Martin; Morotti, Stefano; Lipsett, David B.; Manfra, Ornella; Skogested, Jonas; Aronsen, Jan M.; Sejersted, Ole M.; Sjaastad, Ivar; Edwards, Andrew G.; et al.
Abstract : Rationale: Hypokalemia occurs in up to 20% of hospitalized patients and is associated with increased incidence of ventricular and atrial fibrillation. It is unclear whether these differing types of arrhythmia result from direct and perhaps distinct effects of hypokalemia on cardiomyocytes. Objective: To investigate proarrhythmic mechanisms of hypokalemia in ventricular and atrial myocytes. Methods and Results: Experiments were performed in isolated rat myocytes exposed to simulated hypokalemia conditions (reduction of extracellular [K + ] from 5.0 to 2.7 mmol/L) and supported by mathematical modeling studies. Ventricular cells subjected to hypokalemia exhibited Ca 2+ overload and increased generation of both spontaneous Ca 2+ waves and delayed afterdepolarizations. However, similar Ca 2+ -dependent spontaneous activity during hypokalemia was only observed in a minority of atrial cells that were observed to contain t-tubules. This effect was attributed to close functional pairing of the Na + -K + ATPase and Na + -Ca 2+ exchanger proteins within these structures, as reduction in Na + pump activity locally inhibited Ca 2+ extrusion. Ventricular myocytes and tubulated atrial myocytes additionally exhibited early afterdepolarizations during hypokalemia, associated with Ca 2+ overload. However, early afterdepolarizations also occurred in untubulated atrial cells, despite Ca 2+ quiescence. These phase-3 early afterdepolarizations were rather linked to reactivation of nonequilibrium Na + current, as they were rapidly blocked by tetrodotoxin. Na + current-driven early afterdepolarizations in untubulated atrial cells were enabled by membrane hyperpolarization during hypokalemia and short action potential configurations. Brief action potentials were in turn maintained by ultra-rapid K + current (IKur ); a current which was found to be absent in tubulated atrial myocytes and ventricular myocytes. Conclusions: Distinct mechanisms underlie hypokalemia-induced arrhythmia in the ventricle and atrium but also vary between atrial myocytes depending on subcellular structure and electrophysiology. Abstract : Supplemental Digital Content is available in the text.